Oxford world watch Geography 2 grade 7 - Moorcroft, Christine (Karachi : Oxford university press, 2023)
Oxford World Watch Geography Grade 7 (Second Edition) is a comprehensive geography textbook designed for Grade 7 students. It provides an in-depth exploration of geographical concepts, including physical geography, human geography, and environmental studies. The book focuses on understanding the relationship between people and their environment, as well as the importance of sustainable practices for future generations.
Keywords: Geography : Textbook; Oxford :Grade 7